2004
DOI: 10.1016/j.ejheart.2003.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trials update from the American Heart Association meeting: Ω‐3 fatty acids and arrhythmia risk in patients with an implantable defibrillator, ACTIV in CHF, VALIANT, the Hanover autologous bone marrow transplantation study, SPORTIF V, ORBIT and PAD and DEFINITE

Abstract: The American Heart Association meeting reported the results of several clinical trials of particular interest to those who care for patients with heart failure. V-3 fatty acids were associated with a trend to increased recurrence of ventricular arrhythmias but not mortality in patients with an implantable debrillator. The ACTIV in CHF study provides more evidence of a therapeutic role for arginine vasopressin antagonists in the treatment of heart failure. The VALIANT study provides further evidence to suggest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“…The direction and magnitude of benefit in SCD‐HeFT is consistent with the data from previous, unconfounded studies [9] (Fig. ).…”
Section: Scd‐heft: Sudden Cardiac Death In Heart Failure Trialsupporting
confidence: 89%
“…The direction and magnitude of benefit in SCD‐HeFT is consistent with the data from previous, unconfounded studies [9] (Fig. ).…”
Section: Scd‐heft: Sudden Cardiac Death In Heart Failure Trialsupporting
confidence: 89%
“…Previous studies of fish oil supplementation have shown conflicting results [3,4]. It is possible that the results of this study may have been influenced by the high level of fish consumption in the Japanese population compared to western countries.…”
Section: Repair-ami (Reinfusion Of Enriched Progenitormentioning
confidence: 73%
“…85 ICD therapy reduced allcause mortality at 5 years by 23% in patients with predominantly NYHA class II heart failure and left ventricular systolic dysfunction. 86 There were 244 deaths (29%) in the placebo group, 240 (28%) in the amiodarone group, and 182 (22%, P < 0.007) in the ICD group. 87 Children with DCM constitute up to one-third of patients in pediatric series of ICD therapy, although half of these DCM children go on to device removal at transplantation.…”
Section: Scd-mentioning
confidence: 97%
“…SCD‐HeFT showed a significant reduction of total mortality in the ICD group, whereas amiodarone did not improve survival 85 . ICD therapy reduced all‐cause mortality at 5 years by 23% in patients with predominantly NYHA class II heart failure and left ventricular systolic dysfunction 86 . There were 244 deaths (29%) in the placebo group, 240 (28%) in the amiodarone group, and 182 (22%, P < 0.007) in the ICD group 87 …”
Section: Treatmentmentioning
confidence: 99%